A4.14 Selection and characterisation of rank specific thioaptamers. (13th February 2015) - Andras, J; Simon, L; Redlich, K; Meszaros, T; Mandl, P
Abstract : Background/Objective: The RANK (Receptor Activator of Nuclear Factor kappa B) receptor, located on the surface of osteoclasts plays a critical role in osteoclastogenesis. Aptamers are single-stranded oligonucleotides selected from a random single stranded RNA/DNA library to bind specifically to various targets (e.g. proteins) after folding into well-defined spatial structures. We set out to develop aptamers targeting the RANK receptor, a key marker of osteoclast differentiation. Materials and methods: A single-stranded DNA library (approx. 10 12 different sequences) was amplified via polymerase chain reaction. Thiophosphate-modified deoxynucleotide triphosphates were used in order to generate nuclease-resistant thioaptamers. The glutathione S transferase-tagged, extracellular domain of the human RANK protein (AA 30–212) was produced by in vitro translation. After affinity purification, using this target, thioaptamers were selected by the iterative, in vitro SELEX (Systematic Evolution of Ligands by EXponential enrichment) process. The enriched single-stranded thioaptamer pool was amplified, cloned into bacteria, and 31 clones with inserts corresponding to the size of the aptamer were then sequenced. Thioaptamer candidates were screened by surface plasmon resonance (SPR). Results: Thioaptamers were generated against the extracellular domain of the human RANK protein using the SELEX process. The interaction of nine randomly chosen thioaptamer candidates and their target protein was screened by SPR using the random initial oligonucleotide pool as negative control. A binding event was defined by a reflectivity variation (deltaR%) greater than 0, 1. We identified four thioaptamers, which showed higher reflectivity variation (deltaR% 0.15–0.42), as opposed to the negative control (deltaR% 0.05), representing 1.4–3.9 fmol/mm 2 and 0.5 fmol/mm 2 surface coverage of the protein, respectively. Conclusion: We identified four thioaptamers via the in vitro selection process, SELEX, which can recognise the extracellular domain of the human RANK protein. By further selection using transgenic cell lines and murine osteoclast cultures our aim is to select aptamers, which can specifically bind to both the murine and human RANK protein. Such nuclease-resistant aptamers may facilitate the identification of osteoclast precursors in human serum and may also be of potential therapeutic value as neutralising agents against RANK in murine models of inflammatory bone loss.